Molecular cloning and characterization of a rat brain cDNA encoding a 5-hydroxytryptamine1B receptor. - Voigt, M M (1991)
To date, there have been at least eight different receptors for the neurotransmitter serotonin (5-HT) identified in the central nervous system. These receptors fall into four pharmacological classes: 5-HT1, 5-HT2, 5-HT3 and 5-HT4. The 5-HT1 class has been shown to contain at least four pharmacologically distinct subtypes, 5-HT1A-D. Of these, cDNAs encoding the 5-HT1A and 5-HT1C receptors have been previously characterized. We now report the cloning and expression of a rat brain cDNA encoding another member of the 5-HT1 receptor family. Transient expression of this clone demonstrated high-affinity binding of [3H]5-HT with a pharmacological profile corresponding to that of the 5-HT1B subtype: 5-CT, 5-HT greater than propranolol greater than methysergide greater than rauwolscine greater than 8-OH-DPAT. In situ hybridization revealed expression of cognate mRNA within cells of the dorsal and median raphe nuclei, consistent with previous reports that the 5-HT1B receptor acts as an autoreceptor on 5-HT terminals in this species. mRNA expression was also detected in cells within the CA1 region of hippocampus, striatum, layer 4 of cortex and in the cerebellum, suggesting a previously unrecognized post-synaptic role for the 5-HT1B receptor.